PENGARUH METODE PEMBELAJARAN SQ3R TERHADAP KEMAMPUAN MEMBACA BAHASA JAWA PADA KELAS II DI SDN SIMOMULYO 1 SURABAYA - Mushonnif, Muhammad Hafidz Al; Rulyansah, Afib; Kasiyun, Suharmono; Susanto, Rudi Umar (LPPM Institut Pendidikan Nusantara Global, 2023)
This research is motivated by the inability of students to read Javanese. This happens because the learning of Javanese has not been maximized. This study aims (1) to determine the application of reading ability using the SQ3R method to low grade students at SDN Simomulyo 1 Surabaya, (2) to determine the effect of applying the SQ3R method to reading ability in Javanese in low grade students at SDN Simomulyo 1 Surabaya. This type of research is quantitative research. The population in this study were class II students at SDN Simomulyo I Surabaya, totaling 26 students consisting of 13 male students and 13 female students. Based on the research results, the following two conclusions were concluded (1) the application of reading skills using the SQ3R method in learning at SDN Simomulyo 1 Surabaya involves students being active with teacher guidance, so that the concepts in the discussion can be understood, so as to improve students' reading skills. (2) the ability to read Javanese using the SQ3R Class II method at SDN Simomulyo I Surabaya with an average pre-test is classified as low, this is evident from the student's average score of 61.15. The ability to read Javanese using the SQ3R Class II method at SDN Simomulyo I Surabaya with an average post-test is quite good, this is evident from the students' average score of 80.